Non-contrast MRI perfusion angiosome in diabetic feet. - Zheng, Jie; Hastings, Mary K; Muccigross, David; Fan, Zhaoyang; Gao, Fabao; Curci, John; Hildebolt, Charles F; Mueller, Michael J (European Radiology, 2015)
Objective: The purpose of this study is to develop a non-contrast magnetic resonance imaging (MRI) approach to evaluate skeletal muscle perfusion in the diabetic foot based on the concept of angiosomes of the foot.Methods: Five healthy volunteers and five participants with diabetes (HbA1c = 7.2 ± 1.8%) without a history of peripheral artery disease were examined. The non-contrast perfusion measurements were performed during a toe flexion challenge. Absolute perfusion maps were created and two regions (medial and lateral) on the maps were segmented based on angiosomes.Result: Regional difference in the perfusion of foot muscle was readily visualized in the MRI perfusion angiosomes during the challenge. In the participants with diabetes, the perfusion during toe flexion challenge was significantly lower than in healthy volunteers (P < 0.01). The average perfusion for the medial plantar region of the right foot was lower in subjects with diabetes (38 ± 9 ml/min/100 g) than in healthy subjects (93 ± 33 ml/min/100 g).Conclusions: Non-contrast MRI perfusion angiosome maps demonstrate the feasibility of determining regional perfusion in foot muscles during toe challenge and may facilitate evaluation of muscle perfusion in diabetic feet.Key Points: • Non-contrast MRI perfusion angiosome maps measure regional perfusion in foot muscles non-invasively. • Foot perfusion response to challenge is reduced in persons with diabetes. • MRI perfusion angiosome maps may help evaluation of regional foot muscle perfusion.